Impact of Topology and Traffic on Interference and Routing in IEEE 802.11 Wireless Mesh Network - Feng Zeng; Lan Yao; higang Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Due to the share nature of wireless medium, interference is the critic factor for the performance improvement in wireless mesh networks. In this paper, we address topology and traffic has the impact on the interference, and even routing, and the interference consists of two parts. One is topology-related interference. Another is traffic-related interference. In IEEE 802.11 based wireless mesh networks, topology-related interference is come from the hidden nodes, and quantified by the number of hidden nodes. Taking information from CTS frames, traffic-related interference is defined and quantified. With the integration of topology and traffic related interference, an interference-aware routing metric and protocol is proposed. In route selection, the proposed routing protocol selects the route with the least interference as the data transmission path. Simulation results show that the proposed routing protocol outperforms the other two protocols in terms of network throughput and end-to-end delay. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.870